Analisis regresi linier perilaku dan pelayanan kesehatan dengan sub indeks penyakit tidak menular tahun 2014 (Berita Kedokteran Masyarakat (BKM), 2018)
PHDI (Public Health Development Index) is a picture of progress in the health sector and a further elaboration of the health component of the Human Development Index (HDI) in Indonesia. PHDI 2014 consists of seven component sub-indices which are sub-index of Non Communicable Diseases (NCD). The analytical method used is multiple linear regression, while data from data Basic Health Research (Riskesdas) 2013 and the Potential of Village (PODES) 2011 which are consisted of 497 districts / cities throughout Indonesia. The purpose of analysis is to find the relationship of NCD sub index with behavioral and health services as well as making a prediction value of NCD index variable through independent variables which include the proportion of tobacco consumption, the proportion of properly brushing teeth, the proportion of adequately physical activity, the proportion of the number of doctors in sub-district and the proportion of Health Care Assurance ownership. The analysis showed that the variables such as brushing teeth, physical activity and smoking absence have a significant relationship with the sub-index of NCD (p-value = 0.000) with influence of 10.7%. Variables that have the most impact on the sub-index of NCD is adequately physical activity with a coefficient of 0.002.